RNA-seq analysis revealed considerable genetic diversity and enabled the development of specific KASP markers for Psathyrostachys huashanica - Zhang, Hao; Zeng, Chunyan; Li, Liangxi; Zhu, Wei; Xu, Lili; Wang, Yi; Zeng, Jian; Fan, Xing; Sha, Lina; Wu, Dandan; Cheng, Yiran; Zhang, Haiqin; et al. (Frontiers in Plant Science, 2023)
Psathyrostachys huashanica, which grows exclusively in Huashan, China, is an important wild relative of common wheat that has many desirable traits relevant for wheat breeding. However, the poorly characterized interspecific phylogeny and genomic variations and the relative lack of species-specific molecular markers have limited the utility of P. huashanica as a genetic resource for enhancing wheat germplasm. In this study, we sequenced the P. huashanica transcriptome, resulting in 50,337,570 clean reads that were assembled into 65,617 unigenes, of which 38,428 (58.56%) matched at least one sequence in public databases. The phylogenetic analysis of P. huashanica, Triticeae species, and Poaceae species was conducted using 68 putative orthologous gene clusters. The data revealed the distant evolutionary relationship between P. huashanica and common wheat as well as the substantial diversity between the P. huashanica genome and the wheat D genome. By comparing the transcriptomes of P. huashanica and Chinese Spring, 750,759 candidate SNPs between P. huashanica Ns genes and their common wheat orthologs were identified. Among the 90 SNPs in the exon regions with different functional annotations, 58 (64.4%) were validated as Ns genome-specific SNPs in the common wheat background by KASP genotyping assays. Marker validation analyses indicated that six specific markers can discriminate between P. huashanica and the other wheat-related species. In addition, five markers are unique to P. huashanica, P. juncea, and Leymus species, which carry the Ns genome. The Ns genome-specific markers in a wheat background were also validated regarding their specificity and stability for detecting P. huashanica chromosomes in four wheat–P. huashanica addition lines. Four and eight SNP markers were detected in wheat–P. huashanica 2Ns and 7Ns addition lines, respectively, and one marker was specific to wheat–P. huashanica 3Ns, 4Ns, and 7Ns addition lines. These markers developed using transcriptome data may be used to elucidate the genetic relationships among Psathyrostachys, Leymus, and other closely-related species. They may also facilitate precise introgressions and the high-throughput monitoring of P. huashanica exogenous chromosomes or segments in future crop breeding programs.